The liquid-hydrogen absorber for MICE. (April 2019) - Bayliss, V; Boehm, J; Bradshaw, T; Courthold, M; Harrison, S; Hills, M; Hodgson, P; Ishimoto, S; Kurup, A; Lau, W; Long, K; Macwaters, C; et al.
Abstract: This paper describes the liquid hydrogen system constructed for The Muon Ionization Cooling Experiment (MICE); MICE was built at the STFC Rutherford Appleton Laboratory to demonstrate the principle of muon beam phase-space reduction via ionization cooling. Muon beam cooling will be required at a future proton-derived neutrino factory or muon collider. Ionization cooling is achieved by passing the beam through an energy-absorbing material, such as liquid hydrogen, and then re-accelerating the beam using RF cavities. This paper describes the system creating the 22 l of liquid hydrogen within the MICE beamline; the necessary safety engineering, the liquid hydrogen absorber and its associated cryogenic and gas systems are presented, along with its performance.